UPAYA PENANGGULANGAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA OLEH REMAJA DI POLRESTA DELI SERDANG - Robiyanti, Dewi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The most dangerous crime among teenagers is narcotics abuse. Overcoming the abuse of narcotics and illegal drugs among teenagers is not only the responsibility of the government but also parents, the community and law enforcement officials, especially the police. This type of research is empirical with a sociological approach. The data used are primary and secondary data. Factors that cause the occurrence of criminal acts of drug abuse by teenagers at the Deli Serdang Police are caused by internal factors which include age factors, wrong views and lack of religion in children. In addition there are also external factors, namely family factors, economic factors, environmental factors including social media. Efforts made by the Deli Serdang Police in tackling the occurrence of criminal acts of narcotics abuse by teenagers are preventive efforts consisting of socialization and empowerment efforts to the community. In addition, there are also repressive efforts by eradicating drug kingpins and dealers and rehabilitation. For this reason, it is recommended that teenagers stay away from narcotics and the Police at the Deli Serdang Police must be more active in efforts to overcome them.